PENINGKATAN PRODUKTIVITAS KARYAWAN MELALUI KEPUASAN KERJA, DISIPLIN KERJA DAN MOTIVASI KERJA - Silviyani , Trias; Aminnudin, Moch (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study examines the influence of job satisfaction, work discipline, and work motivation on employee productivity at PT. Urecel Indonesia, a polyurethane foam manufacturer facing productivity fluctuations post-COVID-19. Using a quantitative survey method, data were gathered via Likert-scale questionnaires from 139 slovin sampled employees out of 160, analyzed through Partial Least Squares (PLS) regression via SmartPLS 4. Findings indicate all variables significantly affect productivity: job satisfaction (β=0.236, p<0.001), work discipline (β=0.252, p=0.013), and work motivation (β=0.401, p<0.001), with motivation dominant (R²=0.543). Work motivation explains the most variance, underscoring its primacy in manufacturing contexts. This research provides empirical evidence from Indonesia's sector, recommending firms prioritize motivation enhancement, alongside discipline and satisfaction, for optimal output and sustained performance.